An investigation into Italian consumers' awareness, perception, knowledge of European Union quality certifications, and consumption of agri-food products carrying those certifications - Niculina Iudita Sampalean; Daniele Rama; Giulio Visentin (Bio-based and Applied Economics (BAE), 2021)
The present study investigated Italian consumers' awareness, perception, knowledge of European Union (EU) quality certifications: Protected Designation of Origin (PDO), Protected Geographical Indication (PGI), Traditional Specialty Guaranteed (TSG), and organic as well as the consumption of agri-food products carrying those certifications. A total of 212 consumers responsible for food purchases took part in a web-based survey between June and December 2019, inclusive. Descriptive statistics were calculated in relation to the data collected, followed by a factor analysis to reduce data dimensionality, and a cluster analysis on the latent variables generated, to identify similarities and differences among respondents. Awareness, perception, knowledge and consumption of agri-food products carrying EU quality labels has increased among consumers in recent years. The results related to the consumer's knowledge of quality-certified products showed that more than half of respondents were able to spontaneously quote examples of PDO (76%), PGI (56%) and organic food products (73%) while only 33% of participants could name at least one TSG product. The general awareness of the guarantees offered by PDO and PGI certifications was also assessed in relation to production processes, the natural and human factors of a particular environment and the reputation and quality of a particular region. Cluster analysis showed that consumers with the highest education were most likely to value EU quality certifications and support their local economies. The information obtained have practical implications for marketing and communication of European certified food products at national and international level.
Keywords: 330; factor analysis; cluster analysis; food labels; knowledge evolution; Europe - an quality certifications